Retail Investors Awareness on Stock Market W.R.To Indian Stock market - B.Neeraja,; Chandani, Arti; N.Srividhya,; Rizwana, (International Journal of Psychosocial Rehabilitation, 2020)
India is a developing nation. The recourse required for business so called money is always in scare in such country. People in Indian economy are more sentimental and believe in cultural heritage. We have our own set of perception regarding few concepts. In general investment in stock market is always treated as a risk factor. People who have plenty of money and who are ready to take risk only can invest in stock market is the general assumption though in real world it is not true and if people who analysis the technical and financial details of a company can predict the trend of the market share for that company. Due of lack of proper knowledge and guidance there are many people who burn their figures and create a panic that stock market investment is not a good avenue for parking your funds/ savings.Psychologists have identified many patients who have symptoms of depression is due to stress and unexpected loss either physical or psychological. Out of these patients nearly 40% patients come with a problem associated to financial loss due to debt loss. When people are dealing with significant debt, they are much more likely to report health problems, according to an Associated Press AOL health poll conducted in 2012. Roughly 10 to 16 million people are “suffering terribly due to their debts, and their health is likely to be negatively impacted,” says Paul J. Lavrakas, a research psychologist who analyzed the results of the survey. Lavrakas and his colleagues from the Ohio State University developed the “Debt Stress Index” to track the impact of worry about financial debt on health and well-being. The index hit a record high in July 2011 and has only slowly decreased with the first signs of economic recovery. Among the people reporting high debt stress in the AP poll, 27 % had ulcers or digestive-tract problems, compared with 8 % of those with low levels of debt stress, and 29 % who suffered severe anxiety, compared with 4 % of those with low debt stress. On a more intuitive level, money is more than just cash and coins. Just ask anyone who’s suffered a layoff, witnessed their retirement savings vanish, or watched helplessly as the value of their house plummeted—money provides feelings of security, power, independence, and freedom. And the threat of ongoing debt or insufficient income can result in feelings of loss of control, anxiety, and other mental and emotional distress. In addition, chronic financial stress has been linked to a cycle of increased workplace absenteeism, diminished workplace performance, and depression. This article is to observe the factors of stress related issues and nervous problems due to financial distress. In India most of the patients are directly or indirectly related to share broking. So the group will be identified and the reasons for stress would be